2017
DOI: 10.4172/2150-3508.1000209
|View full text |Cite
|
Sign up to set email alerts
|

Nodaviruses in Wild Fish Population Collected Around Aquaculture Cage Sites from Coastal Areas of Tunisia

Abstract: This report describes the viral epidemiology of wild fish adjacent to cage farms within the Tunisian coasts and is focused on viral nervous necrosis virus (VNNV). A total of 92 apparently healthy wild marine fish were collected near aquaculture facilities in five different coastal areas of Tunisia. The brains and eyes of fish were examined by quantitative real time reverse transcriptase-polymerase chain reaction (qRT-PCR) to detect the nodavirus coat protein gene of. A total of 57 out of 92 (61.9%) samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(66 reference statements)
1
6
1
1
Order By: Relevance
“…In recent The RGNNV genotype, which affects tropical and temperate fish species, is the most widely distributed ( Figure 2) and has the highest number of susceptible species (Tables 1, 2 and 4). In recent years, surveys conducted in different geographical areas have shown that RGNNV is widely distributed Pathogens 2020, 9, 106 6 of 46 not only in farmed but also among wild fish in the Mediterranean basin and along the coasts of Asia and Australia [46,[62][63][64][65][66][67][68][69][70][71][72]. It has also been isolated from farmed white seabass (Atractoscion nobilis) in California [73].…”
Section: Geographical Distribution and Host Rangementioning
confidence: 99%
See 3 more Smart Citations
“…In recent The RGNNV genotype, which affects tropical and temperate fish species, is the most widely distributed ( Figure 2) and has the highest number of susceptible species (Tables 1, 2 and 4). In recent years, surveys conducted in different geographical areas have shown that RGNNV is widely distributed Pathogens 2020, 9, 106 6 of 46 not only in farmed but also among wild fish in the Mediterranean basin and along the coasts of Asia and Australia [46,[62][63][64][65][66][67][68][69][70][71][72]. It has also been isolated from farmed white seabass (Atractoscion nobilis) in California [73].…”
Section: Geographical Distribution and Host Rangementioning
confidence: 99%
“…It is well documented that changes experienced by ecosystems will affect the epidemiology of infectious diseases in animals, in the wild and under intensive farming conditions, including aquaculture [152][153][154][155][156]. The high number of wild asymptomatic species infected with NNV, mainly in Asian and Mediterranean countries [62,64,[66][67][68]71,80,82] and the quick rise in the viral load and subsequent outbreak of mortalities observed in experimentally infected sole when water temperature increased from 16 to 22 • C [148], suggest that VER outbreaks could have dramatic effects on natural populations, as has already been reported for some endangered fish species in the Mediterranean [72,96,109]. On the other hand, it could be argued that ocean warming could decrease the pathologies associated with the BFNNV genotype.…”
Section: Viral Thermotolerancementioning
confidence: 99%
See 2 more Smart Citations
“…Pemutusan siklus hidup dari virus ini di perairan sudah tidak memungkinkan lagi untuk dilakukan. Beberapa ikan liar, plankton, dan krustasea kecil disinyalir dapat menjadi inang perantara bagi virus ini di samping faktor cuaca, lingkungan, dan stres yang membuat kondisi ikan lemah atau rentan terhadap infeksi penyakit (Cherif & Fatma, 2017;Yahunar et al, 2016).…”
Section: Pendahuluanunclassified